Experimental investigation of terahertz scattering: A study of non-Gaussianity and lateral roughness influence - Alissa, Mai; Friederich, Benedikt; Sheikh, Fawad; Czylwik, Andreas; Kaiser, Thomas (IEEE Access, 2020)
The scattering phenomenon caused by rough surfaces has a dominant role in shaping the reflected field at terahertz (THz) frequencies, both in specular and non-specular directions. Most surfaces in nature are randomly rough, and the surface height obeys a certain statistical distribution. A Gaussian probability density function (PDF) for height distribution is often considered, and the correlation length is assumed to be longer than the wavelength. However, a clear understanding of how changing these assumptions affect the angular distribution of the scattered field is still lacking. In the first part of this work we investigate via microscopic measurements the statistical distribution of realistic indoor materials, and its deviation from the assumed normal distribution. After that, the influence of non-Gaussianity on the specular reflection in the low THz region is shown analytically. In the second part, a measurement campaign of diffuse scattering, caused by structured statistically-controlled surfaces, is reported. The correlation length assumption has been proven experimentally and via full-wave simulation to affect the diffuse scattering by rough samples, when the other statistical parameters are kept without changes.
Created from Fastlane, Scopus look-up
Keywords: Non-Gaussian heights' distributions; Scattering measurements; Statistically-controlled rough surfaces; THz communication